2014
DOI: 10.1021/tx500034c
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus in Oropharyngeal Squamous Cell Carcinoma in the United States Across Time

Abstract: Human papillomaviruses (HPVs) are involved in approximately 5% of all human cancer. Although initially recognized for causing nearly all cases of cervical carcinoma, much data has now emerged implicating HPVs as a causal factor in other anogenital cancers as well as a subset of head and neck squamous cell carcinomas (HNSCCs), most commonly oropharyngeal cancers. Numerous clinical trials have demonstrated that patients with HPV+ oropharyngeal squamous cell carcinoma (OPSCC) have improved survival compared to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 62 publications
6
71
1
Order By: Relevance
“…LSCC patients with an HPV-16 single infection most frequently present at an early stage (stage I-II) with advanced node status (N1-N2). Similar results were observed for patients with HNSCC and OPSCC [33,34]. In our study, 28 cases (21.2%) had multiple HPV infections.…”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancersupporting
confidence: 89%
“…LSCC patients with an HPV-16 single infection most frequently present at an early stage (stage I-II) with advanced node status (N1-N2). Similar results were observed for patients with HNSCC and OPSCC [33,34]. In our study, 28 cases (21.2%) had multiple HPV infections.…”
Section: Tong Et Al: Prognostic Significance Of Hpc In Laryngeal Cancersupporting
confidence: 89%
“…In this study, we found an HPV prevalence of 24.3% in our cohort, which is lower than the prevalence in OSCC and tonsillar cancer reported for the USA (45-83%) 4,5 or northern Europe (26-93%), 5,23,24 but comparable to data for central Europe (14-33%) [25][26][27] . We considered HPV-association of samples when high risk HPV-DNA was detected along with p16INK4a expression.…”
Section: Discussioncontrasting
confidence: 64%
“…2,3 A recently published metaanalysis demonstrates a rising incidence of HPV1 OSCC in the United States from 21% (pre-1990), to 51% (1990-1999), to 65% (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013). 4 Patients with HPV-associated OSCC show lower levels of disease recurrence and progression compared to patients with HPV-negative OSCC. Even with good loco regional tumor control, patients with HPV-associated OSCC have similar rates of distant metastases as patients with HPVnegative OSCC.…”
mentioning
confidence: 97%
“…All studies that tested for the presence of HPV in head and neck cancer tissues from patients diagnosed with squamous cell carcinoma of the head and neck (oral cavity, oropharynx, larynx and hypopharynx) were eligible for inclusion in this analysis. The bibliographies of several review articles were also examined in order to identify additional publications that might have been missed by our PubMed search (11)(12)(13)(14)(15). This review identified 291 original articles that qualified conditionally for the analysis.…”
Section: This Study Was Approved By the Fox Chase Cancer Center Instimentioning
confidence: 99%